2019
DOI: 10.1097/md.0000000000016458
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of neonatal acidosis using the cerebroplacental ratio at different gestational weeks

Abstract: We evaluated the clinical value of the cerebroplacental ratio (CPR) in predicting neonatal acidosis according to the gestational weeks in late pregnancy. From July 2016 to June 2017, 1018 neonates without acidosis and 218 neonates with acidosis (confirmed postpartum) underwent a prenatal examination and hospital delivery at 28 to 41 +6 weeks in our hospital. The CPR was calculated as the ratio of the prenatal middle cerebral artery-pulsation index (MCA-PI) to the umbilical art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
1
1
Order By: Relevance
“…In disagreement with our study, Guo, Chai et al 2019 found that CPR cutoff values in 37 to 41+6 weeks was 1.29, 1.36, and 1.22, respectively (21) .…”
Section: Discussioncontrasting
confidence: 99%
“…In disagreement with our study, Guo, Chai et al 2019 found that CPR cutoff values in 37 to 41+6 weeks was 1.29, 1.36, and 1.22, respectively (21) .…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding past references, we were unable to find multivariable studies evaluating predictors of delivery outcome in fetuses examined <34 weeks. Most of previous publications have solely studied the mUtA PI for the prediction of APO especially in preeclampsia [18][19][20][21] or the CPR 22,23 for the prediction of APO in an isolated way. In general, these studies confirm that lower values of CPR and high values of mUtA PI herald APO, although the mUtA PI effect is doubtful in case of AGA 4,25 .…”
Section: Comparison With Existing Literaturementioning
confidence: 99%